2020
DOI: 10.3389/fnmol.2020.603409
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Vector Encoding Neuropeptide Y and Its Receptor Y2 for Future Treatment of Epilepsy: Preclinical Data in Rats

Abstract: Gene therapy to treat pharmacoresistant temporal lobe epilepsy in humans is now being developed using an AAV vector (CG01) that encodes the combination of neuropeptide Y and its antiepileptic receptor Y2. With this in mind, the present study aimed to provide important preclinical data on the effects of CG01 on the duration of transgene expression, cellular tropism, and potential side effects on body weight and cognitive function. The CG01 vector was administered unilaterally into the dorsal and ventral hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…These pitfalls are usually not encountered with therapeutic peptides, which are generally well tolerated because they are specific by design and active at low concentrations [34]. Moreover, a therapeutic peptide can be chronically synthesized by recipient cells following the transfer of a synthetic gene encoding its amino acid sequence [35,36]. Indeed, several gene therapies are currently under evaluation for AD [37] and PD [38], yet they are generally focused on neuroprotection (e.g., [36,39,40]).…”
Section: Introductionmentioning
confidence: 99%
“…These pitfalls are usually not encountered with therapeutic peptides, which are generally well tolerated because they are specific by design and active at low concentrations [34]. Moreover, a therapeutic peptide can be chronically synthesized by recipient cells following the transfer of a synthetic gene encoding its amino acid sequence [35,36]. Indeed, several gene therapies are currently under evaluation for AD [37] and PD [38], yet they are generally focused on neuroprotection (e.g., [36,39,40]).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum dose of NPY was attained after 3 weeks of administration and the level was maintained for up to 26 weeks. Based on the Y maze and Morris test the results also concluded that overexpression of NPY and Y2 mRNA levels did not show any side effects associated with learning, memory, and body weight [91]. A study on the delivery of a combination of single vector-gene therapy in the treatment of Status Epilepticus induced by the Kainic Acid model was done by Melin et al A dose-response study was done to assess an effective dose of the viral particles for seizure suppression in acute seizure model & chronic TLE model.…”
Section: Role Of Neuropeptide Y In Epilepsymentioning
confidence: 86%
“…Deshalb verzögerte sich die weitere Entwicklung dieses Ansatzes bis klar wurde, dass sich diese Nebenwirkung bei bereits erkrankten Tieren nicht zeigt. Die Firmen CombiGene und Spark Therapeutics produzieren nun aktuell unter dem Namen CG01 einen Virus, der für humane Studien verwendet werden soll und mit dessen Dosierung auch gesunde Ratten kein Gedächtnisdefizit mehr aufwiesen [7]. Es wird wahrscheinlich noch einige Jahren dauern, bis hier mit Ergebnissen zu rechnen ist.…”
Section: Npy/y2 üBerexpressionunclassified